Instructional resources for innovative history teaching and learning in Tanzania secondary schools: exploring availability and utilization - Eunice Ndomondo (Cogent Arts & Humanities)
Instructional resources support enormously in the teaching and learning of the history subject. However, scarcity of resources is evidenced to impair effective teaching and learning in many African classrooms. To understand the Tanzanian context, this hermeneutic phenomenological study explored history teachers’ perspectives on the availability of instructional resources and their use in supporting the learning of history subject in secondary schools. The study was conducted with eleven history teachers in six lower secondary schools and data were collected using semi-structured interviews, classroom observation and a review of teachers’ lesson plan books. Content analysis was used to draw meaning from the data. The study revealed an acute shortage of textual and technological resources in all of the studies classrooms, making instructions highly transmission relying on talk, chalk and board. To some of the teachers, inadequate competencies inhibited their use of technological resources. More, insufficient time allocated for the history subject in school calendars limited extensive use of instructional resources. Hence, history was studied as narrations of the past, inhibiting students’ interest, imagination and critical thinking. The findings call for deliberate measures to improve the availability of instructional resources for history teaching in schools. A clear description of instructional resources in the history syllabus, continuous teachers’ training on the use of technological resources and adjustment of the school timetables to provide adequate time for the history subject are also required in improving the utilization of instructional resources in history teaching.